Implementasi Kebijakan Program Jatim Bebas Pasung - Virdean Paulia Pratama; Katerina Bataha (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2024)
The East Java Provincial Social Service prioritizes the shackle-free East Java program. The program seeks to end the practice of shackling. In reality, the shackle problem is still found in East Java. The aim of the research is to examine the execution of the East Java shackles-free policy as a top priority initiative to help shackle victims regain their social function and spiritual well-being. In this work, a case study methodology uses qualitative research. Then, observation, documentation, and interviews were used to collect data. The six indicators used in this research include policy standards and aims, resources, implementing organization characteristics, relationships between organizations, implementers' attitudes, and the social, economic, and political environment. The study's findings indicate that East Java has not yet fully implemented the shackle-free program. It has been established that several districts and cities have not adopted the shackle-free program because social readiness is limiting their ability to do so. That's holding up the goal of East Java to get rid of shackles.